Latent tuberculosis in kidney and liver transplant patients: a review of treatment practices and outcomes. Issue 5 (3rd October 2015) - Grim, S.A.; Layden, J.E.; Roth, P.; Gallitano, S.; Adams, W.; Clark, N.M.
Abstract Background The standard treatment of latent tuberculosis infection (LTBI) is associated with toxicities and data are limited on tolerability among patients with advanced organ disease listed for transplant. Alternate options are available, but they have yet to be studied in this population. Methods A retrospective review of the treatment of LTBI among kidney and/or liver transplant candidates was conducted to assess factors impacting therapy initiation, tolerability, and completion of therapy. Results Of 174 eligible patients, treatment of LTBI was initiated in 129, of which 91 were listed for kidney transplant and 38 were listed for liver or liver/kidney transplant. Infectious Diseases consultation was independently associated with treatment initiation when controlling for waitlisted organ and receipt of hemodialysis (odds ratio [OR] 81.14, 95% confidence interval [CI] 23.94–274.94, P < 0.001). Documented completion of first‐line therapy was 47% overall, and 49% and 39%, respectively, among kidney and liver/kidney candidates (P = not significant). On multivariable analysis, controlling for baseline aspartate aminotransferase and waitlisted organ, first‐line receipt of rifampin was associated with lower rates of treatment completion (OR 0.19, 95% CI 0.05–0.77, P = 0.02). Conclusion Based on medical record documentation, completion of first‐line therapy was <50% in this cohort, although this is likely an underestimate, as 34% of patients had no chart documentation that therapy was completed. Approximately 20% of patients did not complete first‐line therapy because of adverse effects.